RESEARCH PATHWAYS IN NON-FORMAL AND INFORMAL EDUCATION: A SYSTEMATIC LITERATURE REVIEW BETWEEN 2014 AND 2024 - Costiche, Samuel Willlian Schwertner; Alves, Denis Rogério Sanches; Bergold, Arthur William de Brito (Seven Editora, 2026)
Non-formal education is a proposed pedagogical approach aligned with the Brazilian National Common Curriculum Base (BNCC) and the new educational guidelines related to the social, interactive, and autonomous development of the student. The objective of this work is to conduct a literature review on Non-formal and Informal Education between 2014 and 2024, presenting the research paths followed by the works published during this period, contrasting them with the political and educational changes provided by the BNCC. As methodological procedures, we adopted the PICO strategy for formulating research questions, which were answered based on the collection of 51 articles from the CAPES Periodicals Portal and classified according to the identified research paths. The results point to an increase in the number of works published after the consolidation of the BNCC in 2017, and the expansion of non-formal education to non-educational spaces, such as the work and social context. We conclude that the expansion of research in Nonformal Education may be related to the educational changes brought about by the BNCC (National Common Core Curriculum) and that the debate regarding Nonformal Education has gone beyond the limits of teachers’ actions to become a tool for accessing information and valuing traditional knowledge.